2020
DOI: 10.3329/jafmc.v14i2.45909
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pulmonary Tuberculosis among Rohingya Refugees in Kutupalong Camp, Bangladesh

Abstract: Introduction: An estimated over seventy thousands Rohingya refugees living in Bangladesh since August 2017. World Health Organization (WHO) warned that there could be an outbreak of infectious diseases like tuberculosis (TB) among the Rohingya that would also be a threat to the local people. Objectives: To find out the prevalence of TB among Rohingya refugees in Kutupalong camp, Ukhiya. Materials and Methods: This cross-sectional observational study was conducted at the field medical laboratory of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Myanmar is ranked as one of the top 30 countries with the highest levels of tuberculosis infections (Kanabus, 2021;WHO, 2020d). Several studies have shown high prevalences of latent infections in Myanmar and Rohingya refugees (Chaves et al, 2009;Jasmine et al, 2018;Wong & Lee, 2020), whereas levels of active infections were mainly low (Chaves et al, 2009;Jasmine et al, 2018).…”
Section: Infections Spread By Close Contactmentioning
confidence: 99%
“…Myanmar is ranked as one of the top 30 countries with the highest levels of tuberculosis infections (Kanabus, 2021;WHO, 2020d). Several studies have shown high prevalences of latent infections in Myanmar and Rohingya refugees (Chaves et al, 2009;Jasmine et al, 2018;Wong & Lee, 2020), whereas levels of active infections were mainly low (Chaves et al, 2009;Jasmine et al, 2018).…”
Section: Infections Spread By Close Contactmentioning
confidence: 99%
“…In recent years, the number of quantitative studies focused on refugees and host communities has increased dramatically (Verme & Schuettler, 2021). Many of these studies seek to quantify the direct costs of hosting and challenges facing refugees with respect to employment (Alix-Garcia et al, 2018;Fallah, Krafft, and Wahba, 2018), consumption (Maystadt and Verwimp, 2014;Kreibaum, 2016;Mahmud and Nalifa, 2020), health (Baez, 2011;Riley et al, 2017;Chan, Chiu, and Chan, 2018;Jasmine et al, 2020) and local prices (Alix-Garcia & Saah, 2010). More recently, there has been an effort to examine the impacts of the COVID-19 pandemic for refugees and hosts (Bukuluki et al, 2020;Charney, 2020;Islam, Inan, and Islam, 2020;Shammi, Robi, and Tareq, 2020;Vishwanath, Alik-Lagrange, & Aghabarari, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Another study conducted in Nigeria found that the majority of the respondents (85.6%) agreed that people do not go to the clinics in their catchment area for consultation and follow-up out of fear of what they will say about them. 29,30,31 . Crowding, inadequate ventilation, malnutrition, smoking, low socioeconomic status, and HIV infection are all risk factors for TB 32,33,34,36 .…”
mentioning
confidence: 99%